THE FRENCH GEOGRAPHER EMMANUEL DE MARTONNE AND HIS CONTRIBUTION TO ROMANIAN GEOGRAPHY - VASILIȚĂ-CRĂCIUN, Ileana-Cristina (Studia Universitatis Babeș-Bolyai Geographia, 2025)
Emmanuel de Martonne (1873–1955) was a prominent geographer of the 20th century, recognized for his essential contributions to the development of geography as a scientific discipline, his interest in cultural diversity, and his balanced perspective on the relationship between humans and nature. His work is well known not only in France but also internationally. A significant portion of his research focused on the Romanian geographical space. During the interwar period, he played an important role in the delineation of the borders of Greater Romania. Moreover, he distinguished himself by conducting the first detailed analysis of the geography of Romania, with particular emphasis on the Făgăraș Mountains, which he referred to as the “Alps of Transylvania.”